PENGARUH PEMANGKASAN TERHADAP PERTUMBUHAN DAN PRODUKSI BERBAGAI VARIETAS CABAI MERAH (Capsicum annuum L.) - Sukmawati Sukmawati; St. Subaedah; Sudirman Numba (Percetakan Umi Toaha Makassar, 2018)
Red Chilli pepper is one kind of plant that has high economic value, because it is necessary not only for household needs, but also a need for the industry. This research was conducted at the location of Farmers Kelompok Tani Sumber Rezeki, Toddopulia Village, District Tanralili, Maros, which lasted from March to July 2016. The study aims to analyze the effect of pruning on the growth and yield of different varieties of chilli red. This study was designed by Split Plot Design. In the main plot pruning consists of two levels ie without trimming and pruning wild Shoots, as a subplot that varieties of three types: Princes variety, variety Kastilo F1 variety, and Monser F1 variety. The results showed that pruning does not affect the component plant height and the number of productive branches, but a good effect on crop production with a number of fruit crops gained 135.68 fruit, fruit weight per plant was obtained 635.10 g of fruit weight per plot was obtained 10, 85 kg. Weight of fruit per hectare high of 30.15 tons obtained in the interaction between pruning and varietys Princes.